900 MHz Radiofrequency Field Induces Mitochondrial Unfolded Protein Response in Mouse Bone Marrow Stem Cells - Xie, Wen; Xu, Rui; Fan, Caiyun; Yang, Chunyu; Chen, Haiyan; Cao, Yi (Frontiers in Public Health, 2021)
Objective: To examine whether exposure of mouse bone marrow stromal cells (BMSC) to radiofrequency fields used in mobile communication devices can induce mitochondrial unfolded protein response (UPR^mt). Methods: BMSCs were exposed to continuous wave 900 MHz radiofrequency fields (RF) at 120 μW/cm2 power intensity for 4 h/d for 5 consecutive days. To inhibit the upstream molecular JNK2 of UPRmt, cells in siRNA + RF and siRNA + XR group were pretreated with 100nM siRNA-JNK2 for 48 hours before RF/XR exposure. Thirty minutes, four hours and twenty-four hours after RF/XR exposure, cells were collected, the level of ROS was measured with flow cytometry, the expressions of UPRmt-related proteins were detected using Western blot analysis. Results: Compared with Sham group, 30 minutes and 4 hours after RF/XR exposure, the level of ROS in RF and XR group was significantly increased (P<0.05). Compared with Sham group, 30 minutes and 4 hours after RF exposure, the expression levels of HSP10/HSP60/ClpP protein in cells of RF and XR group increased significantly (P<0.05), however 24 hours after RF exposure, the RF/XR-induced increase of HSP10/HSP60/ClpP protein level reversed. After interference with siRNA-JNK2, the RF/XR-induced increase of HSP10/HSP60/ClpP protein level reversed. Conclusions: The exposure of 900 MHz low-dose microwave radiation could increase ROS level and activate UPR^mt in BMSC cells. The increased HSP10/HSP60/ClpP protein level last up to 4 hours. 24 hours after RF exposure, mitochondrial homeostasis is restored. However, the detailed underlying molecular mechanism of RF-induced UPR^mt remains to be further studied.